KRITIK WACANA TAFSIR ATAS TEOLOGI KESETARAAN GENDER RIFFAT HASSAN - Ikrar Ikrar (IAIN Manado, 2022)
Abstract: This article discuss about how theology construct worked by Riffat Hassan to realize gender equality and how the implication caused from gender equality and how the relation of women harmony in Islam. Based on the result, it can be concluded that (1) Theology construct of gender equality built by Riffat Hassan, only adopt from feminism theology concept that developed in Western. Even though in western, women have dark history because woman have been despised and treated discriminatory, and while women in Islam are glorified. The coming of Islam has eliminated dumb tradition that harmful for women, but elevate the dignity. If subordination of women in western has gained legitimacy from Bible, in Al – Qur’an women are precisely glorified. (2) In building gender equality theology, Riffat Hassan has made three steps; (a) normative-idealist approach, (b) deconstruct religious thought that he thinks there’s gender bias, (c) reconstruct religious thought that he thinks there’s no gender bias. In attempt this theology construct of gender equality, Riffat Hassan precisely proven tend to do gender bias, although he accuse travelers do gender bias. Beside that, there are some of implications that caused by him; there are rejection of authentic hadith and the implication that could change Islamic law. (3) As for in Islam, the right relation between women and men are the harmony of gender, not gender equality. Keywords: Gender Equality, Riffat HassanAbstrak: Artikel ini membehas tentang bagaimana konstruksi teologi yang dilakukan oleh Riffat Hassan untuk mewujudkan kesetaraan gender dan bagaimana implikasi yang ditimbulkan dari kesetaraan gender serta bagaimana hubungan keserasian perempuan dalam Islam. Berdasarkan hasil pembahasan dapat disimpulkan bahwa (1) Konstruksi teologi kesetaraan gender yang dibangun Riffat Hassan hanyalah mengadopsi konsep teologi feminisme yang berkembang di Barat. Padahal berbeda dengan perempuan di Barat yang memiliki sejarah yang kelam lantaran perempuan dipandang hina dan diperlakukan secara diskriminatif, dalam Islam perempuan justru dimuliakan. Kedatangan Islam telah mengeliminasi adat-istiadat jahiliyah yang merugikan kaum perempuan serta mengangkat harkat dan martabat mereka. Kalau subordinasi terhadap perempuan di Barat mendapatkan legitimasi dari Bible, dalam al-Quran perempuan justru dimuliakan. (2) Dalam membangun teologi kesetaraan gender, Riffat Hassan melakukan tiga langkah, yaitu (a) pendekatan normatif-idealis dan historis-empiris, (b) melakukan dekonstruksi pemikiran keagamaan yang (menurutnya) bias gender, dan (c) melakukan rekonstruksi pemikiran keagamaan yang (menurutnya) tidak bias gender. Dalam usaha konstruksi teologi kesetaraan gender ini, Riffat Hassan justru terbukti cendrung melakukan bias gender, padahal dia menuduh para mufassir yang bias gender. Selain itu, ada beberapa implikasi yang ditimbulkan darinya, yaitu adanya penolakan terhadap hadis shahih dan terdapat implikasi syariah yang merubah hukum Islam.(3) Adapun dalam Islam, hubungan antara laki-laki dan perempuan yang benar adalah keserasian gender, bukan kesetaraan gender. Kata Kunci: Kesetaraan Gender, Riffat Hassan